NETosis of psoriasis: a critical step in amplifying the inflammatory response - Zhang, Jinke; Feng, Yahui; Shi, Dongmei (Frontiers in Immunology, 2024)
NETosis, a regulated form of neutrophil death, is crucial for host defense against pathogens. However, the release of neutrophil extracellular traps (NETs) during NETosis can have detrimental effects on surrounding tissues and contribute to the pro-inflammatory response, in addition to their role in controlling microbes. Although it is well-established that the IL-23-Th17 axis plays a key role in the pathogenesis of psoriasis, emerging evidence suggests that psoriasis, as an autoinflammatory disease, is also associated with NETosis. The purpose of this review is to provide a comprehensive understanding of the mechanisms underlying NETosis in psoriasis. It will cover topics such as the formation of NETs, immune cells involved in NETosis, and potential biomarkers as prognostic/predicting factors in psoriasis. By analyzing the intricate relationship between NETosis and psoriasis, this review also aims to identify novel possibilities targeting NETosis for the treatment of psoriasis.